Trends on conventional and modern breeding techniques of Brassica vegetables - Kishor Varotariya; Mottaiyan Pitchaimuthu (Journal of Oilseed Brassica, 2025)
Vegetable crops, particularly those of the cole variety, serve as pivotal entities in the exploitation of heterosis to engineer high-yielding hybrids. Despite their inherent significance, challenges such as labor intensity and a dearth of skilled personnel hinder large-scale hybrid seed production endeavors. Cole crops, belonging to the Brassicaceae family, exhibit discernible heterotic responses, displaying attributes such as augmented yield, uniform maturation, precocious flowering, and robustness against diverse stressors. Employing controlled pollination techniques, notably selfincompatibility mechanisms and genetic emasculation methods, stands as the cornerstone of economically viable commercial hybrid seed production practices. This comprehensive review delves into the intricate genetic underpinnings governing mechanisms such as genic male sterility, cytoplasmic male sterility, self-incompatibility, and the application of chemical hybridizing agents in cole crops. A critical appraisal of the merits and demerits of these strategies ensues, with a particular focus on cost-effective modalities for large-scale F1 seed generation. Prominent examples include hybrids such as Pusa Cabbage Hybrid 1, Pusa Cabbage Hybrid 81, and Pusa Snowball Hybrid 1 and 2, cultivated by leading public sector entities and private seed enterprises. Moreover, this review explores advanced biotechnological methodologies, including tissue culture, somatic hybridization, molecular-assisted breeding, genetic engineering, RNAi, and genome editing, aimed at augmenting crucifer improvement programs.